2020
DOI: 10.1002/jbm.b.34598
|View full text |Cite
|
Sign up to set email alerts
|

Achieving enhanced bone regeneration using monetite granules with bone anabolic drug conjugates (C3 and C6) in rat mandibular defects

Abstract: Bone grafting procedures are commonly used to manage bone defects in the craniofacial region. Monetite is an excellent biomaterial option for bone grafting, however, it is limited by lack of osteoinduction. Several molecules can be incorporated within the monetite matrix to promote bone regeneration. The aim was to investigate whether incorporating bone forming drug conjugates (C3 and C6) within monetite can improve their ability to regenerate bone in bone defects. Bilateral bone defects were created in the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The potential of 4 for local administration has been demonstrated in recently published studies where brushite and monetite preloaded with 4 have demonstrated significant efficacy to enhance implant integration in a rabbit calvarial implant model . Other recent studies have shown that Bio-Oss and monetite loaded with 4 or 7 can significantly speed and enhance bone repair in a rat mandible critical bone defect model …”
Section: Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The potential of 4 for local administration has been demonstrated in recently published studies where brushite and monetite preloaded with 4 have demonstrated significant efficacy to enhance implant integration in a rabbit calvarial implant model . Other recent studies have shown that Bio-Oss and monetite loaded with 4 or 7 can significantly speed and enhance bone repair in a rat mandible critical bone defect model …”
Section: Results and Discussionmentioning
confidence: 96%
“…29 Other recent studies have shown that Bio-Oss and monetite loaded with 4 or 7 can significantly speed and enhance bone repair in a rat mandible critical bone defect model. 30 ■ EXPERIMENTAL SECTION Chemistry. General Information.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, synthetic anabolic bone-forming drug conjugates (C3 and C6), consisting of an enhanced bone activator of the prostaglandin E2 receptor and inactive bisphosphonate, were reported to be beneficial for bone regeneration. In one study, C3 and C6 were encapsulated within monetite (consisting of β-tricalcium phosphate (β-TCP) and monocalcium phosphate monohydrate (MCPM), respectively) to improve osteoinductivity in a mandibular bone defect model in Sprague-Dawley rats 101 , and the results showed that monetite+C6 resulted in the highest bone repair percentage (~42%, compared with~32% in monetite+C3 and~22% in the control group) at 4 weeks. This research provided proof-of-concept for a novel therapy that combined bone anabolic drugs with biodegradable monetite, and it also identified a promising therapeutic direction for bone repair after maxillofacial tumour surgery in the future (Fig.…”
Section: Traditional Novelmentioning
confidence: 99%
“…Among various types of calcium phosphate, hydroxyapatite (Ca10(PO4)6(OH)2) has received much attention in the field of bone tissue engineering since it exhibits good biocompatibility, biological activity, and osteoconductivity [20][21][22]. In addition to hydroxyapatite, dicalcium phosphate (CaHPO4) or monetite is another type of calcium phosphate that has attracted significant interest over the past years since it can regenerate the bond and also resorb in vivo faster than other calcium phosphates [23][24][25]. Moreover, monetite in a powder form is used in some toothpastes, chewing gums, and the food processing industries [26].…”
Section: Introductionmentioning
confidence: 99%